1996
DOI: 10.1093/ajcp/105.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Reduced E-Cadherin Expression is Associated With Invasiveness and Unfavorable Prognosis in Breast Cancer

Abstract: A s s o c i a t e d W i t h I n v a s i v e n e s s a n dU n f a v o r a b l e P r o g n o s i s i n B r e a s t C a n c e r high histologic grade (chi square test for trend, P <.001), negative estrogen receptor status (ER; Fisher's exact test, P = .042), and marginally with axillary node involvement (Fisher's exact test, P = .063). In a subset of 109 primary IDC patients whose clinical follow-up was available (median follow-up 51 months), reduced E-cad expression was associated with shortened disease-free sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
208
4
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(235 citation statements)
references
References 20 publications
20
208
4
3
Order By: Relevance
“…E-cadherin is thought to act as a tumor suppressor gene in the breast, although the mechanism of E-cadherin-mediated tumor suppression has not been fully elucidated (17). Previous reports showed low expression of E-cadherin in breast cancers with increased invasiveness and high metastatic potential (13,14). Our results are in agreement with the literature in the sense that the non-IBC tumors with angiolymphatic invasion and/or metastases had significantly less E-cadherin expression than the tumors that did not have these features.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…E-cadherin is thought to act as a tumor suppressor gene in the breast, although the mechanism of E-cadherin-mediated tumor suppression has not been fully elucidated (17). Previous reports showed low expression of E-cadherin in breast cancers with increased invasiveness and high metastatic potential (13,14). Our results are in agreement with the literature in the sense that the non-IBC tumors with angiolymphatic invasion and/or metastases had significantly less E-cadherin expression than the tumors that did not have these features.…”
Section: Discussionsupporting
confidence: 92%
“…Diminished E-cadherin expression has been related to the acquisition of invasiveness in experimental tumors and in advanced-stage carcinomas, including ductal carcinomas of the breast (7)(8)(9)(10)(11)(12). Several studies have shown that E-cadherin expression is significantly reduced in high-grade, estrogen receptor (ER)-negative, and metastatic breast carcinomas (10,13,14). Loss of E-cadherin expression tends to appear in a heterogeneous pattern within carcinomas, suggesting that loss of expression of E-cadherin in these tumors is a potentially reversible somatic alteration.…”
mentioning
confidence: 99%
“…Decreased E-cadherin expression is associated with a more aggressive behaviour of breast cancer (Siitonen et al, 1996). The homotypic cellular adhesion molecule E-cadherin is a transmembrane glycoprotein important for the organisation of epithelial structure (Takeichi, 1995;Huber et al, 1996;Yagi and Takeichi, 2000).…”
mentioning
confidence: 99%
“…Subsequent studies have shown loss of E-cadherin expression is a common ®nding in a wide spectrum of human epithelial cancers (Birchmeier and Behrens, 1994). In breast cancer, loss of E-cadherin expression has been correlated with a more invasive phentoype and a less di erentiated histology (Siitonen et al, 1996;Gamallo et al, 1993). Recent studies have provided more compelling evidence that E-cadherin inactivation does not simply re¯ect the cancer phenotype, but, in fact, Ecadherin inactivation has a causal role in the process.…”
mentioning
confidence: 99%